Measles in adults: A comparison of hospitalised HIV-infected and HIV-uninfected patients - Nina E. Diana; Charles Feldman (AOSIS, 2019)
Background: Although measles is traditionally a childhood illness, there are an increasing number of adult cases. Despite both measles and HIV infection being endemic in sub-Saharan Africa, there are little data regarding outcomes in co-infected patients. Objectives: Compare demographic, clinical, laboratory and radiographic features, as well as outcome (length of hospital stay, complications and mortality) between HIV-infected and HIV-uninfected adult patients admitted with confirmed measles. Methods: We conducted a retrospective record review of adult patients with confirmed measles who were admitted to the Infectious Diseases Unit at the Charlotte Maxeke Johannesburg Academic Hospital during the peak of the 2009 and 2010 South African measles outbreak. The data collected included demographic, clinical and laboratory parameters, as well as outcomes. Results: Of the 33 confirmed measles cases admitted, 24 patients were tested for HIV infection and 18 tested seropositive. There were no significant differences in the demographics, clinical findings or laboratory data when comparing the HIV-positive and HIV-negative cases. Serious clinical manifestations were seen more frequently in HIV-positive patients (odds ratio [OR] 5, 95% confidence interval [CI] 0.48-51.8, p = 0.34). One of the six patients testing HIV-negative developed pneumonia, while six of the 18 HIV-positive patients had a course complicated by pneumonia. Five of these HIV-positive patients required admission to the intensive care unit, three developing respiratory failure necessitating mechanical ventilation. HIV-positive patients had several other manifestations, including acute kidney injury, purulent conjunctivitis, pancreatitis and encephalitis. HIV-positive patients had a significantly longer hospital stay (p = 0.03). There were three deaths in the HIV-positive group, but none in the HIV-negative group (OR 2.9, 95% CI 0.13-65.3, p = 0.55). Conclusion: Our study provides data on the largest series of hospitalised adults infected with HIV and co-infected with measles. More severe consequences seemed to occur in hospitalised HIV-positive patients.